2000
DOI: 10.1590/s0103-50532000000600006
|View full text |Cite
|
Sign up to set email alerts
|

Chemical defenses of the endemic Brazilian gorgonian Lophogorgia violacea Pallas (Octocorallia, Gorgonacea)

Abstract: O mecanismo de defesa contra predadores no octocoral brasileiro Lophogorgia violacea foi investigado através de ensaios de preferência alimentar em campo frente a predadores. Os ensaios de palatabilidade com o extrato bruto da gorgônia demonstraram que seus metabólitos secundários possuem atividade deterrente significativa frente a peixes generalistas. O fracionamento do extrato bruto, guiado pelos ensaios em campo, revelou que uma mistura complexa de furanocembranolídeos é a responsável pela defesa química de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…265 A similar study of the endemic Brazilian gorgonian Lophogorgia violacea using field feeding assays for bioassay-guided fractionation yielded a mixture of 5 furanocembranoid diterpenes that appear to deter fish predation in an additive manner. 267 Crude extracts from common species of gorgonians collected in the Caribbean, 281 " 282 Singapore, 283 and the Pacific, 270 ' 284 have been surveyed for predator deterrent activity in laboratory assays against a generalist predator or in field assays against natural assemblages of reef fishes. The earliest survey demonstrated that approximately 60% of the extracts tested deterred feeding by Thalassoma bifasciatum at natural concentrations determined as the percentage of dry mass.…”
mentioning
confidence: 99%
“…265 A similar study of the endemic Brazilian gorgonian Lophogorgia violacea using field feeding assays for bioassay-guided fractionation yielded a mixture of 5 furanocembranoid diterpenes that appear to deter fish predation in an additive manner. 267 Crude extracts from common species of gorgonians collected in the Caribbean, 281 " 282 Singapore, 283 and the Pacific, 270 ' 284 have been surveyed for predator deterrent activity in laboratory assays against a generalist predator or in field assays against natural assemblages of reef fishes. The earliest survey demonstrated that approximately 60% of the extracts tested deterred feeding by Thalassoma bifasciatum at natural concentrations determined as the percentage of dry mass.…”
mentioning
confidence: 99%
“…265 A similar study of the endemic Brazilian gorgonian Lophogorgia violacea using field feeding assays for bioassay-guided fractionation yielded a mixture of 5 furanocembranoid diterpenes that appear to deter fish predation in an additive manner. 267 This mixture included two new furanocembranoids, 7-acetoxy-hydroxylophotoxin 76 and 3-methoxy-8-hydroxylophotoxin 77 and the known compounds, lophotoxin 78, deoxylophotoxin 79 and 13-acetoxy-11P, 12P-epoxypukalide 80. Crude extracts from common species of gorgonians collected in the Caribbean, 281 " 282 Singapore, 283 and the Pacific, 270 ' 284 have been surveyed for predator deterrent activity in laboratory assays against a generalist predator or in field assays against natural assemblages of reef fishes.…”
mentioning
confidence: 99%
“…52, 58-63, 627-631, 640-644 [24,29,179,184] Eunicea pinta 333-340 [104] Eunicea knighti 163-165 [63] Eunicea mammosa 161, 162, 203, 321-332 [62,[100][101][102][103] Eunicea succinea 158-160, 202, 311-320, 620 [61,98,99] Eunicea tourniforti 36-39 [19] Leptogorgia sp. 482-487, 519 [147,148] Leptogorgia alba 473, 474 [138] Leptogorgia laxa 155, 156 [59] Leptogorgia setacea 475, 476 [142] Lophogorgia peruana 157, 462-471, 526 [60,[137][138][139][140]143] Pseudopterogorgia sp. 532 [159] Pseudopterogorgia bipinnata 531, 619 [158] Pseudopterogorgia kallos 527-530 [134] Gorgonacea Plexaura flexuvsa 557 [163] Sea pen Gyrophyllum sibogae 66, 67 [31] Pseudopterogorgia acerosa 477 [143] Tetralophuzia setifomis 106 […”
Section: Resultsmentioning
confidence: 99%
“…Coralloidolide A (460) and B (461)was isolated from the Mediterranean alcyonacean Alcyonium coralloides [136]. The chemical study of the gorgonian Lophogorgia peruana collected at the Gulf of California has led to the isolation of the five new diterpenes, lophodiol A, lophodiol B, 17-acetoxylophotoxin, 15,16-epoxylophotoxin, and 17-acetoxy-15, 16-epoxylophotoxin (462-466) [60], along with the known com-pounds, lophotoxin (467) [137,138], lopholide (468) [138,139], deoxylophotoxin (469) [140], and the lophotoxin analogs 470 and 471 [140]. Pukalide (472), isolated from the soft coral Sinularia abrupt, is a diterpenoid with a cembrane skeleton, bearing butenolide, epoxide, isopropenyl, and an unprecedented , -disubstituted furan--carboxylate function [141].…”
Section: Furanocembranoidsmentioning
confidence: 99%